Subjectivity as Treatment: Neurosis and the Roots of Contemporary Ethnographic Conservation - Daniel Cull (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This paper explores an imagined ‘origin story’ for ethnographic conservation; exploring the relationships between museums, conservators, indigenous peoples, and ‘ethnographic collections’. Tracing the ‘conservation idea’ from its origins in a state of neurosis to our contemporary post-modern condition, the paper aims to highlight the process through which wounds are being healed and museums along with the profession of conservation are being re-imagined. In so doing the paper explores the increasing realization of the subjectivity of the past, whilst acting as one such subjective his-story.